2003
DOI: 10.1081/ceh-120017928
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Associated with Reduced Plasma Thrombomodulin Levels and a Hypercoagulable State in Rats

Abstract: The plasma thrombomodulin (TM) level, an indicator of systemic endothelial cell damage, was measured in spontaneously hypertensive rats (SHR), deoxycorticosteron acetate (DOCA)-induced hypertensive rats and normotensive Wistar-Kyoto (WKY) rats to clarify its changes in hypertension. Plasma TM levels, measured by enzyme-linked immuno-sorbent assay, decreased with aging (5-20-weeks-old) in both SHR and WKY, and they were lower in SHR than age-matched WKY in all ages examined. Deoxycorticosteron acetate-induced h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…In our study, we observed increased TAT levels after chronic Ang II infusion. Consistent with our findings, it was shown that AT 1 receptor stimulation and HTN was linked to increased activation of coagulation due to increased TF expression and thrombin generation [1113, 16, 17], which led to a pro-thrombotic phenotype [14]. Another possible activator is the non-canonical activation of PAR-1 by matrix-metalloproteinases (MMPs) 1 or 13 [7].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, we observed increased TAT levels after chronic Ang II infusion. Consistent with our findings, it was shown that AT 1 receptor stimulation and HTN was linked to increased activation of coagulation due to increased TF expression and thrombin generation [1113, 16, 17], which led to a pro-thrombotic phenotype [14]. Another possible activator is the non-canonical activation of PAR-1 by matrix-metalloproteinases (MMPs) 1 or 13 [7].…”
Section: Discussionsupporting
confidence: 81%
“…Human HTN patients and animal models of HTN showed enhanced thrombin generation in plasma as measured by elevated thrombin-antithrombin (TAT) complexes [16, 17]. In addition to its important role in both hemostasis and thrombosis, thrombin can induce multiple cellular responses via activation of protease activated receptors, such as PAR-1 [7, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombin-antithrombin complexes levels were found previously to be elevated in SHR plasma. 10 In the present study, thrombin-antithrombin complexes levels and thrombin generation in plasma were no higher in SHR than in Wistar, suggesting a vascular bed-specific effect in the hypertension-associated prothrombotic state. Our observation of an endothelial alteration indicated by elevated circulating levels of vWF in adult SHR compared with Wistar rats leads us to consider that vascular cells could enhance thrombin generation in SHR.…”
Section: Discussionmentioning
confidence: 60%
“…[6][7][8] In spontaneously hypertensive rats (SHR), in deoxycorticosterone acetate-induced hypertensive rats, and in endothelial dysfunction-induced experimental hypertension, a hypercoagulable state was demonstrated by elevated levels of thrombin-antithrombin complexes, as well as d-dimers, and supported by an increase in TF 9 and a decrease in thrombomodulin. 10 In experimental models of hypertension, the direct contribution of vascular cells to thrombin generation is not well documented. Early works focused primarily on the increased vascular expression of TF and antifibrinolytic molecules.…”
mentioning
confidence: 99%
“…An elevated fibrin monomer polymerization rate is associated with ischemic cerebrovascular disease and is an independent risk factor for this disease (24). Sawada et al reported that the plasma levels of thrombomodulin, which is localized to endothelial cells as a receptor of thrombin, decreased due to endothelial injury in deoxycorticosteron acetate-treated hypertensive rats (25). In addition, the blood prothrombin time was significantly shorter in SHR than WKY (26).…”
Section: Discussionmentioning
confidence: 99%